Competition and facilitation between the marine nitrogen-fixing cyanobacterium Cyanothece and its associated bacterial community - Brauer, Verena S.; Stomp, Maayke; Bouvier, Thierry; Fouilland, Eric; Leboulanger, Christophe; Confurius-Guns, Veronique; Weissing, Franz J.; Stal, LucasJ.; Huisman, Jef (Frontiers in Microbiology, 2015)
N2-fixing cyanobacteria represent a major source of new nitrogen and carbon for marine microbial communities, but little is known about their ecological interactions with associated microbiota. In this study we investigated the interactions between the unicellular N2-fixing cyanobacterium Cyanothece sp. Miami BG043511 and its associated free-living chemotrophic bacteria at different concentrations of nitrate and dissolved organic carbon (DOC) and different temperatures. High temperature strongly stimulated the growth of Cyanothece, but had less effect on the growth and community composition of the chemotrophic bacteria. Conversely, nitrate and carbon addition did not significantly increase the abundance of Cyanothece, but strongly affected the abundance and species composition of the associated chemotrophic bacteria. In nitrate-free medium the associated bacterial community was co-dominated by the putative diazotroph Mesorhizobium and the putative aerobic anoxygenic phototroph Erythrobacter and after addition of organic carbon also by the Flavobacterium Muricauda. Addition of nitrate shifted the composition toward co-dominance by Erythrobacter and the Gammaproteobacterium Marinobacter. Our results indicate that Cyanothece modified the species composition of its associated bacteria through a combination of competition and facilitation. Furthermore, within the bacterial community, niche differentiation appeared to play an important role, contributing to the coexistence of a variety of different functional groups. An important implication of these findings is that changes in nitrogen and carbon availability due to, e.g., eutrophication and climate change are likely to have a major impact on the species composition of the bacterial community associated with N2-fixing cyanobacteria.